2020
DOI: 10.3389/fpsyt.2020.00098
|View full text |Cite
|
Sign up to set email alerts
|

Altered Global Brain Functional Connectivity in Drug-Naive Patients With Obsessive-Compulsive Disorder

Abstract: Abnormal functional connectivity (FC) within discrete brain networks is involved in the pathophysiology of obsessive-compulsive disorder (OCD) with inconsistent results. In the present study, we investigated the FC patterns of 40 drug-naive patients with OCD and 38 healthy controls (HCs) through an unbiased voxel-wise global brain FC (GFC) analysis at rest. Compared with HCs, patients with OCD showed decreased GFC within the default mode network (DMN) (i.e., left posterior cingulate cortex/lingual gyrus) and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 53 publications
1
24
0
Order By: Relevance
“…In addition, some researchers found that OCD is related to the sensorimotor network (i.e., precentral gyrus/SMA) (Cui et al, 2020 ). Morein-Zamir et al ( 2016 ) reported that the activation from the regions of the brain within the sensorimotor network in the inhibitory control processes may explain the essence of inhibitory control deficits of OCD.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some researchers found that OCD is related to the sensorimotor network (i.e., precentral gyrus/SMA) (Cui et al, 2020 ). Morein-Zamir et al ( 2016 ) reported that the activation from the regions of the brain within the sensorimotor network in the inhibitory control processes may explain the essence of inhibitory control deficits of OCD.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the hypothesis, the present study found altered asymmetry of intra-hemispheric FC outside the CSTC circuits in patients with OCD. These brain regions are involved in the default mode network (DMN; i.e., left PCC), executive control network (ECN; i.e., left IPL), sensorimotor network (i.e., left precentral gyrus/postcentral gyrus), and cerebellum network (i.e., left cerebellum Crus I), which might participate in the pathophysiology of OCD ( Cui et al, 2020 ). Increased FC is regarded as a dedifferentiation and/or compensatory reallocation to the dysfunction ( Guo et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Next to alterations in attention to food stimuli, we found that active stimulation leads to reduced FC in left amygdala, bilateral insula, left hippocampus, left NAcc and bilateral OFC for sweet foods. The insula and OFC have previously been found activated by the memory of rewarding effects of food and by the taste of palatable food 44–47. Several studies pointed to the key role of the OFC in decision-making for rewards, and it appears to be responsible for cost-benefit calculations and rewarding value of taste 44–46.…”
Section: Discussionmentioning
confidence: 99%